Autograph letter signed from Hans von Bülow - Bülow, Hans von, 1830-1894:::Creator:::::::::::: (2021)
Autograph letter signed from Hans von Bülow to an unidentified recipient, Heidelberg, March 31, 1888. Discusses concert programming and includes a musical quotation of the "Muss es sein?" motto from Beethoven's String quartet, op. 135.